Fine‐scale habitat heterogeneity influences browsing damage by elephant and giraffe. (14th September 2020) - Kimuyu, Duncan M.; Kenfack, David; Musili, Paul M.; Ang'ila, Robert O.
Abstract: Effects of large mammalian herbivores on woody vegetation tend to be heterogeneous in space and time, but the factors that drive such heterogeneity are poorly understood. We examined the influence of fine‐scale habitat heterogeneity on the distribution and browsing effects of two of the largest African terrestrial mammals, the elephant and giraffe. We conducted this study within a 120‐ha (500 x 2, 400 m) ForestGEO long‐term vegetation monitoring plot located at Mpala Research Center, Kenya. The plot traverses three distinct topographic habitats ("plateau, " "steep slopes, " and "valley") with contrasting elevation, slope, soil properties, and vegetation composition. To quantify browsing damage, we focused on Acacia mellifera, a palatable tree species that occurs across the three habitat categories. Overall tree density, species richness, and diversity were highest on the steep slopes and lowest on the plateau. Acacia mellifera trees were tallest and had the lowest number of stems per tree on the steep slopes. Both elephant and giraffe avoided the steep slopes, and their activity was higher during the wet season than during the dry season. Browsing damage on Acacia mellifera was lowest on the steep slopes. Elephant browsing damage was highest in the valley, whereas giraffe browsing damage was highest on the plateau. Our findings suggest that fine‐scale habitat heterogeneity is an important factor in predicting the distribution of large herbivores and their effects on vegetation and may interact with other drivers such as edaphic variations to influence local variation in vegetation structure and composition.